SMARCA4‐deficient lung tumour that presented with haemoptysis and progressed rapidly. Issue 7 (31st August 2020) - Inoue, Mari; Enomoto, Tatsuji; Kawamoto, Masashi; Mikami, Naoto; Kuribayashi, Hidehiko; Saeki, Noriyuki
Abstract: The case of a heavy ex‐smoking man in his early 70s who presented with haemoptysis and died following rapid progression is presented. The tumour excised by surgery was mostly composed of monotonous large rhabdoid cells showing prominent nucleoli and eosinophilic cytoplasm. On immunohistochemistry with SMARCA4 (BRG‐1), the tumour cells showed significant loss of expression. The tumour was diagnosed as a SMARCA4‐deficient thoracic sarcoma. This is a disease that progresses rapidly and has a poor prognosis. However, the search for specific treatments using synthetic lethality is underway. Clinical and pathological characteristics can be identified with examination of more cases, and when the tumour is suspected, it is necessary to actively perform immunohistochemical examination. Abstract : We present the case of a heavy ex‐smoking man in his early 70s who presented with haemoptysis and died following rapid progression. The excised tumour was diagnosed as a SMARCA4‐deficient thoracic sarcoma. This is a disease that progresses rapidly and has a poor prognosis.